1999
DOI: 10.1556/avet.47.1999.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Sensitive Detection of Trypanosoma Evansi by Polymerase Chain Reaction

Abstract: The mechanically transmitted haemoflagellate, Trypanosoma evansi causes surra, a wasting disease of domestic animals and is highly endemic in distribution in Southeast Asia. The detection of T. evansi is important for improving the epizootiological and animal health status of the region. The specificity and sensitivity of polymerase chain reaction (PCR) using oligonucleotide primers constructed from T. evansi repetitive DNA sequences were studied in the present investigation. Using the assay, it was possible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Trypanozoon specific primers have been designed previously: TBR primers which target a 177 bp repeat [4], pMUTEC primers targeting a retrotransposon [5] and ORPHON primers which target the spliced leader sequence [6]. Most of them have been tested on cattle [7,8], water buffaloes [9] or goats [10]. PCR tests for diagnosis of T. congolense and T. vivax infections exist as well [11].…”
Section: Introductionmentioning
confidence: 99%
“…Trypanozoon specific primers have been designed previously: TBR primers which target a 177 bp repeat [4], pMUTEC primers targeting a retrotransposon [5] and ORPHON primers which target the spliced leader sequence [6]. Most of them have been tested on cattle [7,8], water buffaloes [9] or goats [10]. PCR tests for diagnosis of T. congolense and T. vivax infections exist as well [11].…”
Section: Introductionmentioning
confidence: 99%
“…The specificity studies indicated that the primary specific 821-bp and the nested 270-bp PCR products were not amplified even from concentrations of 10 ng of DNA from other blood parasite including Thieleria annulata, Babesia bigemina and blood cells from non infected mice and camels under the same stringency condition described in this study. Based on these sensitivity and specificity results of this study, the described nPCR should be considered as the most highly sensitive and specific assay compared to the previously described PCR-based detection assays [ 10 , 12 , 13 , 19 ]. The second amplification step using the nested primers TE3 and TE4 is necessary to confirm the specificity of the primary amplified product and to increase the sensitivity of the PCR-based assay by at least 1000 times particularly, when the concentration of the T. evansi DNA in the sample is less than 10 pg.…”
Section: Discussionmentioning
confidence: 86%
“…The economic importance of T. evansi infection is mainly attributed to clinical disease in camels in many parts of the world [ 14 - 18 ]. PCR has been used successfully in detecting infection with T. evansi in buffaloes [ 12 , 19 ], horses [ 13 ] and in camels [ 11 ]. So far, there is no comprehensive data on the use of PCR for detecting infection in Sudanese breed of dromedary camels ( Camelus dromedarius ).…”
Section: Discussionmentioning
confidence: 99%
“…The further confirmation of the identity of the candidate trypanosome by PCR through using primers that specifically targeted the ITS1 region of the rDNA gene of T. evansi that is performed in the present study, is similar to the result reported by Croof [50] who used molecular method (PCR) in his study of 40 camels which were tested parasitologically and serologically where 90% of them were found to be positive. PCR has been used in detection of infection with T. evansi in buffaloes [51][52] , in horses [53] and in camels [54] . There was no comprehensive data on the use of PCR for detection of infection in Sudanese breed of dromedary camels (Camelus dromedarius).…”
Section: Discussionmentioning
confidence: 99%